Curable resin composition and display device
By optimizing the molecular weight and acid value of the resin in the resilient resin composition and using specific photopolymerized initiator and antioxidant, the problem of extended development time of the light emission film under thick coating conditions is solved, and the effect of high development speed and high light emission intensity is achieved.
Patent Information
- Application Number
- JP2020210285
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-26
- Filing Date
- 2020-12-18
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2040-12-18
AI Technical Summary
When preparing a light emitting film using existing resilient resin compositions, increasing the coating thickness to increase the light emitting intensity can lead to an extended development time.
Restorable resin compositions containing quantum dots (A), repairable resin (B), photopolymerizable compound (C), photopolymerized initiator (D), antioxidant (E), leveling agent (F) and solvent (G) were used, wherein the molecular weight-weight average value of the resin (B) was less than 10,000 and the acid value was between 90 mgKOH/g and 150 mgKOH/g, and oxygen-imes-like photopolymerized initiator and phosphoric acid/phenol composite antioxidant were used in the composition.
It realizes that under thick coating conditions, the light emitting film has a high development speed and high light emitting intensity, solving the problem of extended development time.
Smart Images

Figure 0007659390000001 
Figure 0007659390000002 
Figure 0007659390000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a curable resin composition, and further to a cured film thereof and a display device including the same. [Background technology]
[0002] Patent Document 1 describes a curable resin composition containing quantum dots. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2016-065178 A Summary of the Invention [Problem to be solved by the invention]
[0004] When forming a cured film using the curable resin composition described in Patent Document 1, if the thickness of the applied film of the curable resin composition is increased in order to increase the luminescence intensity, the development time may become longer.
[0005] An object of the present invention is to provide a curable resin composition which can provide a film having a short development time and high luminescence intensity even when it is thick. [Means for solving the problem]
[0006] The present invention provides the following curable resin composition, cured film, display device, and method for producing the curable resin composition. [1] A composition comprising quantum dots (A), a resin (B), a photopolymerizable compound (C), a photopolymerization initiator (D), an antioxidant (E), a leveling agent (F) and a solvent (G), The resin (B) is a curable resin composition having a weight average molecular weight in terms of polystyrene of less than 10,000 and an acid value of 90 mgKOH / g or more and 150 mgKOH / g or less. [2] The curable resin composition according to [1], wherein the resin (B) includes a resin having an acrylic equivalent of 300 g / eq or more and 2,000 g / eq or less. [3] The curable resin composition according to [1] or [2], wherein a mass ratio of the resin (B) to the photopolymerizable compound (C) is 1 or more. [4] The curable resin composition according to any one of [1] to [3], wherein the photopolymerization initiator (D) contains an oxime compound. [5] The curable resin composition according to any one of [1] to [4], wherein the antioxidant (E) contains a phosphorus / phenol complex type antioxidant. [6] The curable resin composition according to any one of [1] to [5], wherein the leveling agent (F) contains a fluorine-based surfactant or a silicone-based surfactant. [7] The curable resin composition according to any one of [1] to [6], which does not contain any aliphatic tertiary amine compound and any aliphatic quaternary ammonium salt compound, or contains at least one of an aliphatic tertiary amine compound and an aliphatic quaternary ammonium salt compound in an amount of less than 0.4 mass% relative to the total amount of solids in the curable resin composition. [8] A cured film formed from the curable resin composition according to any one of [1] to [7]. [9] A display device comprising the cured film according to [8].
[10] A method for producing the curable resin composition according to [1], comprising the steps of: The resin (B) is prepared. The resin (B) does not contain any aliphatic tertiary amine compound or aliphatic quaternary ammonium salt compound, or contains at least one of an aliphatic tertiary amine compound and an aliphatic quaternary ammonium salt compound in an amount of less than 0.8 mass% based on the total amount of solids in the resin (B).
[11] The method according to
[10] , wherein in the step of preparing the resin (B), no amine compound is used as a reaction catalyst. Effect of the Invention
[0007] According to the present invention, it is possible to provide a curable resin composition which allows the formation of a film having a high luminescence intensity and which can be developed quickly even in a thick film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] <Curable resin composition> The curable resin composition according to the present invention contains quantum dots (A), a resin (B), a photopolymerizable compound (C), a photopolymerization initiator (D), an antioxidant (E), a leveling agent (F) and a solvent (G).
[0009] [1] Quantum dots (A) The quantum dots (A) are semiconductor microparticles having a particle diameter of 1 nm to 100 nm, which utilize the band gap of the semiconductor to absorb ultraviolet light or visible light and emit light. Quantum dots (A) include CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, HgS, HgSe, HgTe, CdHgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, C dZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZn compounds between group 12 elements and group 16 elements, such as SeTe and HgZnSTe; compounds between group 13 elements and group 15 elements, such as GaN, GaP, GaAs, AlN, AlP, AlAs, InN, InP, InAs, GaNP, GaNAs, GaPAs, AlNP, AlNAs, AlPAs, InNP, InNAs, InPAs, GaAlNP, GaAlNAs, GaAlPAs, GaInNP, GaInNAs, GaInPAs, InAlNP, InAlNAs, InAlPAs; and compounds between group 14 elements and group 16 elements, such as PdS and PbSe. When the quantum dots (A) contain S or Se, quantum dots whose surfaces are modified with metal oxides or organic substances may be used. By using surface-modified quantum dots, it is possible to prevent S or Se from being extracted by reactive components in the material forming the organic layer. The quantum dots (A) may also form a core-shell structure by combining the above compounds, such as fine particles having a core of CdSe and a shell of ZnS.
[0010] Since the energy state of quantum dots (A) depends on their size, it is possible to freely select the emission wavelength by changing the particle diameter. For example, in the case of quantum dots composed only of CdSe, the peak wavelengths of the fluorescence spectrum when the particle diameters are 2.3 nm, 3.0 nm, 3.8 nm, and 4.6 nm are 528 nm, 570 nm, 592 nm, and 637 nm, respectively. In addition, the emission light from quantum dots (A) has a narrow spectral width, and by combining light with such steep peaks, the color gamut that can be displayed by the display device is expanded. Furthermore, quantum dots (A) have high responsiveness, and can efficiently utilize the light emitted from the light source. The curable resin composition of the present invention may contain only quantum dots that emit light of a specific wavelength when exposed to light from a light source, or may contain a combination of two or more types of quantum dots that emit light of different wavelengths. Examples of the light of the specific wavelength include red light, green light, and blue light.
[0011] The content of the quantum dots (A) may be, for example, 0.1% by mass or more and 60% by mass or less, preferably 5% by mass or more and 50% by mass or less, more preferably 20% by mass or more and 45% by mass or less, based on the total amount of solids in the curable resin composition. In this specification, the total amount of solids means the sum of the curable resin composition components excluding the solvent (G) described later. The content in the solids of the curable resin composition can be measured by a known analytical means such as liquid chromatography or gas chromatography.
[0012] [2] Resin (B) The polystyrene-equivalent weight average molecular weight of the resin (B) is less than 10000, and may be, for example, 9000 or less. When the resin (B) has the above polystyrene-equivalent weight average molecular weight, a film having a high development speed and high luminescence intensity even in a thick film tends to be obtained. The polystyrene-equivalent weight average molecular weight of the resin (B) may be, for example, in the range of 1000 to 9000, and is preferably in the range of 2000 to 8500, more preferably 3000 to 8500, from the viewpoint of development speed and luminescence intensity. The polystyrene-equivalent weight average molecular weight of the resin (B) is measured according to the measurement method in the Examples section described later. When the resin (B) has a polystyrene-equivalent weight average molecular weight within the above range, a film in which the amount of outgassing released by heating is reduced tends to be obtained. When the resin (B) has a polystyrene-equivalent weight average molecular weight within the above range, a film exhibiting excellent solvent resistance tends to be obtained.
[0013] The acid value of the resin (B) is in the range of 90 mgKOH / g or more and 150 mgKOH / g or less based on the solid content. If the acid value is less than 90 mgKOH / g, the solubility in an alkaline developer is low, and there is a risk of leaving a residue on the substrate, and if the acid value exceeds 150 mgKOH / g, there is a high possibility of the pattern peeling. From the viewpoint of developability, the acid value of the resin (B) is preferably in the range of 95 mgKOH / g or more and 140 mgKOH / g or less, and more preferably in the range of 100 mgKOH / g or more and 130 mgKOH / g or less. Here, the acid value is a value measured as the amount (mg) of potassium hydroxide required to neutralize 1 g of the resin (D), and can be determined, for example, by titration using an aqueous potassium hydroxide solution. The acid value of the resin (B) is measured according to the measurement method in the Examples section described later. When the resin (B) has an acid value within the above range, a film exhibiting excellent solvent resistance tends to be easily obtained.
[0014] The molecular weight distribution of the resin (B) [weight average molecular weight (Mw) / number average molecular weight (Mn)] may be, for example, from 1.0 to 6.0, and from the viewpoint of developability, is preferably from 1.2 to 4.0.
[0015] Examples of the resin (B) include the following resins [K1] to [K4]. Resin [K1]: a copolymer of at least one (a) selected from the group consisting of unsaturated carboxylic acids and unsaturated carboxylic anhydrides (hereinafter sometimes referred to as "(a)") and a monomer (c) (however different from (a)) copolymerizable with (a) (hereinafter sometimes referred to as "(c)"); Resin [K2]: a resin obtained by reacting a copolymer of (a) and (c) with a monomer (b) (hereinafter sometimes referred to as "(b)") having a cyclic ether structure having 2 to 4 carbon atoms and an ethylenically unsaturated bond; Resin [K3]: a resin obtained by reacting a copolymer of (b) and (c) with (a); Resin [K4]: A resin obtained by reacting a copolymer of (b) and (c) with (a) and then with a carboxylic acid anhydride.
[0016] Specific examples of (a) include unsaturated monocarboxylic acids such as (meth)acrylic acid, crotonic acid, o-, m-, and p-vinylbenzoic acid; Unsaturated dicarboxylic acids such as maleic acid, fumaric acid, citraconic acid, mesaconic acid, itaconic acid, 3-vinylphthalic acid, 4-vinylphthalic acid, 3,4,5,6-tetrahydrophthalic acid, 1,2,3,6-tetrahydrophthalic acid, dimethyltetrahydrophthalic acid, and 1,4-cyclohexenedicarboxylic acid; Bicyclounsaturated compounds containing a carboxy group, such as methyl-5-norbornene-2,3-dicarboxylic acid, 5-carboxybicyclo[2.2.1]hept-2-ene, 5,6-dicarboxybicyclo[2.2.1]hept-2-ene, 5-carboxy-5-methylbicyclo[2.2.1]hept-2-ene, 5-carboxy-5-ethylbicyclo[2.2.1]hept-2-ene, 5-carboxy-6-methylbicyclo[2.2.1]hept-2-ene, and 5-carboxy-6-ethylbicyclo[2.2.1]hept-2-ene; Unsaturated dicarboxylic acid anhydrides such as maleic anhydride, citraconic anhydride, itaconic anhydride, 3-vinylphthalic anhydride, 4-vinylphthalic anhydride, 3,4,5,6-tetrahydrophthalic anhydride, 1,2,3,6-tetrahydrophthalic anhydride, dimethyltetrahydrophthalic anhydride, and 5,6-dicarboxybicyclo[2.2.1]hept-2-ene anhydride; Unsaturated mono[(meth)acryloyloxyalkyl] esters of divalent or higher polyvalent carboxylic acids, such as mono[2-(meth)acryloyloxyethyl] succinate and mono[2-(meth)acryloyloxyethyl] phthalate; Examples include unsaturated acrylates that contain a hydroxy group and a carboxy group in the same molecule, such as α-(hydroxymethyl)acrylic acid. Among these, (meth)acrylic acid, maleic anhydride, etc. are preferred from the standpoint of copolymerization reactivity and solubility of the resulting resin in an alkaline aqueous solution. Here, (meth)acrylic acid means acrylic acid and / or methacrylic acid. Hereinafter, the same applies to "(meth)acryloyl", "(meth)acrylate", etc.
[0017] (b) is, for example, a monomer having a cyclic ether structure having 2 to 4 carbon atoms (for example, at least one selected from the group consisting of an oxirane ring, an oxetane ring, and a tetrahydrofuran ring) and an ethylenically unsaturated bond. (b) is preferably a monomer having a cyclic ether structure having 2 to 4 carbon atoms and a (meth)acryloyloxy group.
[0018] Examples of (b) include glycidyl (meth)acrylate, β-methyl glycidyl (meth)acrylate, β-ethyl glycidyl (meth)acrylate, glycidyl vinyl ether, o-vinylbenzyl glycidyl ether, m-vinylbenzyl glycidyl ether, p-vinylbenzyl glycidyl ether, α-methyl-o-vinylbenzyl glycidyl ether, α-methyl-m-vinylbenzyl glycidyl ether, α-methyl-p-vinylbenzyl glycidyl ether, 2,3-bis(glycidyloxymethyl)styrene, 2,4-bis(glycidyloxymethyl)styrene, 2,5-bis(glycidyloxymethyl)styrene, 2,6-bis(glycidyloxymethyl)styrene, 2,3,4-tris(glycidyloxymethyl)styrene, 2,3,5-tris(glycidyloxymethyl)styrene, 2,3,6-tris(glycidyloxymethyl)styrene, 3,4,5-tris(glycidyloxymethyl)styrene, 3,5,6-tris(glycidyloxymethyl)styrene, 3,6,7-tris(glycidyloxymethyl)styrene, 3,7,8-tris(glycidyloxymethyl)styrene, 3,8,9-tris(glycidyloxymethyl)styrene, 3,9,10-tris(glycidyloxymethyl)styrene, 3,10,11-tris(glycidyloxymethyl)styrene, 3,11,12-tris(glycidyloxymethyl)styrene, 3,12,13-tris(glycidyloxymethyl)styrene, 3,13,14-tris(glycidyloxymethyl)styrene, 3,14,15-tris(glycidyloxymethyl)styrene, 3,15,16-tris(glycidyloxymethyl)styrene, 3,16,17-tris(glycidyloxymethyl)styrene Monomers having an oxirane ring and an ethylenically unsaturated bond, such as 2,4,6-tris(glycidyloxymethyl)styrene and 2,4,6-tris(glycidyloxymethyl)styrene; 3-methyl-3-methacryloyloxymethyloxetane, 3-methyl-3-acryloyloxymethyloxetane, 3-ethyl-3-methacryloyloxymethyloxetane, 3-ethyl-3-acryloyloxymethyloxetane, 3-methyl-3-methacryloyloxyethyloxetane, 3-methyl- Examples of the monomer include monomers having an oxetane ring and an ethylenically unsaturated bond, such as 3-acryloyloxyethyloxetane, 3-ethyl-3-methacryloyloxyethyloxetane, and 3-ethyl-3-acryloyloxyethyloxetane; and monomers having a tetrahydrofuran ring and an ethylenically unsaturated bond, such as tetrahydrofurfuryl acrylate (e.g., Viscoat V#150, manufactured by Osaka Organic Chemical Industry Co., Ltd.) and tetrahydrofurfuryl methacrylate. A monomer having an oxirane ring and an ethylenically unsaturated bond is preferred as (b) since the reactivity during production of the resins [K2] to [K4] is high and unreacted (b) is unlikely to remain.
[0019] Examples of (c) include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-methylcyclohexyl (meth)acrylate, tricyclo[5.2.1.02,6]decan-8-yl (meth)acrylate (known in the art as the common name "dicyclopentanyl (meth)acrylate"). (Meth)acrylic acid esters such as tricyclo[5.2.1.02,6]decene-8-yl(meth)acrylate (commonly known in the art as "dicyclopentenyl(meth)acrylate"), dicyclopentanyloxyethyl(meth)acrylate, isobornyl(meth)acrylate, adamantyl(meth)acrylate, allyl(meth)acrylate, propargyl(meth)acrylate, phenyl(meth)acrylate, naphthyl(meth)acrylate, and benzyl(meth)acrylate; hydroxy group-containing (meth)acrylic acid esters such as 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate; dicarboxylic acid diesters such as diethyl maleate, diethyl fumarate, and diethyl itaconate; Bicyclo[2.2.1]hept-2-ene, 5-methylbicyclo[2.2.1]hept-2-ene, 5-ethylbicyclo[2.2.1]hept-2-ene, 5-hydroxybicyclo[2.2.1]hept-2-ene, 5-hydroxymethylbicyclo[2.2.1]hept-2-ene, 5-(2'-hydroxyethyl)bicyclo[2.2.1]hept-2-ene, 5-methoxybicyclo[2.2.1]hept-2-ene chloro[2.2.1]hept-2-ene, 5-ethoxybicyclo[2.2.1]hept-2-ene, 5,6-dihydroxybicyclo[2.2.1]hept-2-ene, 5,6-di(hydroxymethyl)bicyclo[2.2.1]hept-2-ene, 5,6-di(2'-hydroxyethyl)bicyclo[2.2.1]hept-2-ene, 5,6-dimethoxybicyclo[2.2.1]hept -2-ene, 5,6-diethoxybicyclo[2.2.1]hept-2-ene, 5-hydroxy-5-methylbicyclo[2.2.1]hept-2-ene, 5-hydroxy-5-ethylbicyclo[2.2.1]hept-2-ene, 5-hydroxymethyl-5-methylbicyclo[2.2.1]hept-2-ene, 5-tert-butoxycarbonylbicyclo[2.2.1]hept-2-ene, bicyclounsaturated compounds such as ene, 5-cyclohexyloxycarbonylbicyclo[2.2.1]hept-2-ene, 5-phenoxycarbonylbicyclo[2.2.1]hept-2-ene, 5,6-bis(tert-butoxycarbonyl)bicyclo[2.2.1]hept-2-ene, and 5,6-bis(cyclohexyloxycarbonyl)bicyclo[2.2.1]hept-2-ene; dicarbonyl imide derivatives such as N-phenylmaleimide, N-cyclohexylmaleimide, N-benzylmaleimide, N-succinimidyl-3-maleimidobenzoate, N-succinimidyl-4-maleimidobutyrate, N-succinimidyl-6-maleimidocaproate, N-succinimidyl-3-maleimidopropionate, and N-(9-acridinyl)maleimide; Examples of the copolymer include styrene, α-methylstyrene, m-methylstyrene, p-methylstyrene, vinyltoluene, p-methoxystyrene, acrylonitrile, methacrylonitrile, vinyl chloride, vinylidene chloride, acrylamide, methacrylamide, vinyl acetate, 1,3-butadiene isoprene, and 2,3-dimethyl-1,3-butadiene. Among these, styrene, vinyltoluene, N-phenylmaleimide, N-cyclohexylmaleimide, N-benzylmaleimide, bicyclo[2.2.1]hept-2-ene, and the like are preferred from the standpoint of copolymerization reactivity and heat resistance.
[0020] In the resin [K1], the ratio of structural units derived from each of them is as follows among all structural units constituting the resin [K1]: Structural units derived from (a): 2 mol % or more and 60 mol % or less Structural units derived from (c): 40 mol % or more and 98 mol % or less It is preferred that Structural units derived from (a): 10 mol % or more and 50 mol % or less Structural units derived from (c): 50 mol % or more and 90 mol % or less It is more preferable that: When the ratio of the structural units in the resin [K1] is within the above range, the storage stability of the curable composition, the developability when forming a cured pattern, and the solvent resistance of the obtained cured pattern tend to be excellent.
[0021] Resin [K1] can be produced, for example, by referring to the method described in the literature "Experimental Methods of Polymer Synthesis" (written by Takayuki Otsu, published by Kagaku Dojin Co., Ltd., 1st edition, 1st printing, published on March 1, 1972) and the references cited in said literature.
[0022] Specifically, a method is exemplified in which a predetermined amount of (a) and (c), a polymerization initiator, a solvent, etc. are placed in a reaction vessel, and the atmosphere is deoxygenated by, for example, replacing oxygen with nitrogen, and the mixture is heated and kept warm while stirring. The polymerization initiator and solvent used here are not particularly limited, and those that are commonly used in the field can be used. For example, examples of the polymerization initiator include azo compounds (2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), etc.) and organic peroxides (benzoyl peroxide, etc.), and examples of the solvent include those that dissolve each monomer, such as the solvent (H) described below that may be included in the curable composition of the present invention.
[0023] The obtained copolymer may be used as a solution after the reaction as it is, or may be a concentrated or diluted solution, or may be extracted as a solid (powder) by a method such as reprecipitation. In particular, by using a solvent (G) described later as a solvent for this polymerization, the solution after the reaction can be used as it is for the preparation of the curable composition of the present invention, and therefore the production process of the curable composition of the present invention can be simplified.
[0024] Resin [K2] can be produced by obtaining a copolymer of (a) and (c), and then adding the cyclic ether having 2 to 4 carbon atoms contained in (b) to the carboxylic acid and / or carboxylic acid anhydride contained in (a). First, a copolymer of (a) and (c) is produced in the same manner as described for the production method of resin [K1]. In this case, the ratio of the structural units derived from each is preferably the same as that described for resin [K1].
[0025] Next, a part of the carboxylic acid and / or carboxylic acid anhydride derived from (a) in the copolymer is reacted with a cyclic ether having 2 to 4 carbon atoms contained in (b). Following the production of the copolymer of (a) and (c), the atmosphere in the flask is replaced with air from nitrogen, and (b) is reacted in the presence of a reaction catalyst (e.g., an organic phosphorus compound, a metal complex, an amine compound, etc.) between a carboxylic acid or a carboxylic acid anhydride and a cyclic ether and a polymerization inhibitor (e.g., hydroquinone, etc.) at a temperature of 60°C or higher and 130°C or lower for 1 to 10 hours, for example, to produce a resin [K2]. The amount of (b) used is preferably 5 to 80 mol, more preferably 10 to 75 mol, relative to 100 mol of (a). By using this range, the storage stability of the curable composition, the developability when forming a cured pattern, and the balance of the solvent resistance, heat resistance, mechanical strength, and sensitivity of the obtained cured pattern tend to be good. As the organic phosphorus compound as the reaction catalyst, for example, triphenylphosphine can be used. As the amine compound as the reaction catalyst, for example, aliphatic tertiary amine compounds and aliphatic quaternary ammonium salt compounds can be used, and specific examples thereof include tris(dimethylaminomethyl)phenol, triethylamine, tetrabutylammonium bromide, and tetrabutylammonium chloride. From the viewpoint of developability and luminescence intensity, organic phosphorus compounds are preferred. The amount of the reaction catalyst used is preferably 0.001 to 5 parts by mass based on 100 parts by mass of the total of (a), (b) and (c). The amount of the polymerization inhibitor used is preferably 0.001 to 5 parts by mass based on 100 parts by mass of the total of (a), (b) and (c). The reaction conditions such as the charging method, reaction temperature and time can be appropriately adjusted in consideration of the production equipment, the amount of heat generated by the polymerization, etc. As with the polymerization conditions, the charging method and reaction temperature can be appropriately adjusted in consideration of the production equipment, the amount of heat generated by the polymerization, etc.
[0026] Resin [K3] is produced in the first step by the same method as the above-mentioned resin [K1] to obtain a copolymer of (b) and (c). As in the above, the obtained copolymer may be used as it is in the form of a solution after the reaction, or may be a concentrated or diluted solution, or may be extracted as a solid (powder) by a method such as reprecipitation. The ratios of the structural units derived from (b) and (c) to the total number of moles of all structural units constituting the copolymer are, respectively, Structural units derived from (b): 5 mol % or more and 95 mol % or less Structural units derived from (c): 5 mol % or more and 95 mol % or less It is preferred that Structural units derived from (b): 10 mol % or more and 90 mol % or less Structural units derived from (c): 10 mol % or more and 90 mol % or less It is more preferable that:
[0027] Furthermore, under the same conditions as in the manufacturing method of the resin [K2], the cyclic ether derived from (b) contained in the copolymer of (b) and (c) is reacted with the carboxylic acid or carboxylic anhydride contained in (a), thereby obtaining the resin [K3]. The amount of (a) used to react with the copolymer is preferably 5 moles or more and 80 moles or less per 100 moles of (b).
[0028] Resin [K4] is a resin obtained by further reacting resin [K3] with a carboxylic acid anhydride. The hydroxyl group generated by the reaction of a cyclic ether with a carboxylic acid or a carboxylic acid anhydride is reacted with the carboxylic acid anhydride. Examples of the carboxylic acid anhydride include maleic anhydride, citraconic anhydride, itaconic anhydride, 3-vinylphthalic anhydride, 4-vinylphthalic anhydride, 3,4,5,6-tetrahydrophthalic anhydride, 1,2,3,6-tetrahydrophthalic anhydride, dimethyltetrahydrophthalic anhydride, 5,6-dicarboxybicyclo[2.2.1]hept-2-ene anhydride, etc. The amount of the carboxylic acid anhydride used is preferably 0.5 to 1 mole per mole of the amount of (a) used.
[0029] Specific examples of the resin [K1], the resin [K2], the resin [K3] and the resin [K4] include resin [K1] such as a benzyl (meth)acrylate / (meth)acrylic acid copolymer and a styrene / (meth)acrylic acid copolymer; a resin obtained by adding glycidyl (meth)acrylate to a benzyl (meth)acrylate / (meth)acrylic acid copolymer; a resin obtained by adding glycidyl (meth)acrylate to a tricyclodecyl (meth)acrylate / styrene / (meth)acrylic acid copolymer; Resins such as resins to which glycidyl (meth)acrylate has been added [K2]; resins obtained by reacting a copolymer of tricyclodecyl (meth)acrylate / glycidyl (meth)acrylate with (meth)acrylic acid, resins obtained by reacting a copolymer of tricyclodecyl (meth)acrylate / styrene / glycidyl (meth)acrylate with (meth)acrylic acid [K3]; and resins obtained by reacting a copolymer of tricyclodecyl (meth)acrylate / glycidyl (meth)acrylate with (meth)acrylic acid and further reacting the resulting copolymer with tetrahydrophthalic anhydride [K4]. Among these, it is preferable that the resin (B) contains at least one selected from the group consisting of the resin [K2], the resin [K3] and the resin [K4].
[0030] Further examples of the resin (B) include the alkali-soluble resin described in JP 2018-123274 A. Specifically, a polymer (hereinafter also referred to as resin (Ba)) having a double bond in a side chain, containing a structural unit (α) represented by the following general formula (I) and a structural unit (β) represented by the following general formula (II) in the main chain, and further containing an acid group can be mentioned. The acid group can be introduced into the resin, for example, by the resin (Ba) containing a structural unit (γ) derived from an acid group-containing monomer (e.g., (meth)acrylic acid, etc.). The resin (Ba) preferably contains the structural units (α), (β) and (γ) in the main chain skeleton. [ka] [In the formula, R 1 and R 2 are the same or different and represent a hydrogen atom or a hydrocarbon group having 1 to 25 carbon atoms. n represents the average number of repeating units of the structural unit represented by general formula (I) and is a number of 1 or more. [ka] [In the formula, R 3 R may be the same or different and represents a hydrogen atom or a methyl group. 4 are the same or different and represent a linear or branched hydrocarbon group having 4 to 20 carbon atoms. m represents the average number of repeating units of the structural unit represented by general formula (II) and is a number of 1 or more.
[0031] In the resin (Ba), the content of the structural unit (α) may be, for example, from 0.5% by mass to 50% by mass, preferably from 1% by mass to 40% by mass, more preferably from 5% by mass to 30% by mass, based on the total amount of all monomer units that provide the main chain skeleton of the resin (Ba) from the viewpoint of heat resistance and storage stability. In the general formula (I), n represents the average number of repeating units of the structural unit (α) in the resin (Ba), and n can be set so that the content of the structural unit (α) falls within the above range.
[0032] From the viewpoint of solvent resistance, the content of the structural unit (β) may be, for example, 10% by mass or more and 90% by mass or less, preferably 20% by mass or more and 80% by mass or less, more preferably 30% by mass or more and 75% by mass or less, based on the total amount of all monomer units that provide the main chain skeleton of the resin (Ba), 100% by mass. m in the general formula (II) represents the average number of repeating units of the structural unit (β) in the resin (Ba), and m can be set so that the content of the structural unit (β) falls within the above-mentioned range.
[0033] From the viewpoint of solubility in alkaline substances and solubility in solvents, the content of the structural unit (γ) may be, for example, 0.5% by mass or more and 50% by mass or less, preferably 2% by mass or more and 50% by mass or less, and more preferably 5% by mass or more and 45% by mass or less, relative to 100% by mass of the total amount of all monomer units that provide the main chain skeleton of the resin (Ba).
[0034] The resin (B) can include one or more resins selected from the group consisting of the above-mentioned resin [K1], resin [K2], resin [K3], resin [K4] and resin (Ba).
[0035] In order to adjust the weight average molecular weight of resin (B) to 9,000 or less, reaction conditions such as the selection of raw materials to be used, the charging method, reaction temperature and time can be appropriately combined and adjusted.
[0036] The resin (B) may contain a resin having an acrylic equivalent of, for example, 300 g / eq or more and 2000 g / eq or less (hereinafter, also referred to as an acrylic resin). The acrylic resin preferably has an acrylic equivalent of 500 g / eq or more and 1500 g / eq or less. When the resin (B) contains an acrylic resin, it tends to be easier to prevent development that causes quenching during the color filter process. On the other hand, when the resin (B) contains a resin having an acrylic equivalent exceeding 2000 g / eq, it tends to be difficult to obtain the ability to effectively protect the quantum dots, and when the resin (B) contains a resin having an acrylic equivalent less than the above range, it tends to be easily peeled off without being dissolved during development. Preferably, the resin (B) is an acrylic resin. When the resin (B) has an acrylic equivalent within the above range, it tends to be easier to obtain a film in which the amount of outgassing released by heating is reduced. When the resin (B) has an acrylic equivalent within the above range, it tends to be easier to obtain a film that exhibits excellent solvent resistance.
[0037] The content of the resin (B) in the curable resin composition may be, for example, 5% by mass or more and 80% by mass or less, preferably 10% by mass or more and 70% by mass or less, more preferably 13% by mass or more and 60% by mass or less, and even more preferably 17% by mass or more and 55% by mass or less, based on the total amount of solids in the curable resin composition. When the content of the resin (B) is within the above range, the quantum dots tend to be easily dispersed and the luminous efficiency tends to be easily maintained high during the process.
[0038] From the viewpoint of developability and luminous intensity, the resin (B) preferably does not contain any aliphatic tertiary amine compound and any aliphatic quaternary ammonium salt compound, or contains at least one of an aliphatic tertiary amine compound and an aliphatic quaternary ammonium salt compound in an amount of less than 0.4 mass% based on the total amount of solids in the curable resin composition. From the viewpoint of developability and luminous intensity, the curable resin composition preferably does not contain any aliphatic tertiary amine compound and any aliphatic quaternary ammonium salt compound, or contains at least one of an aliphatic tertiary amine compound and an aliphatic quaternary ammonium salt compound in an amount of less than 0.4 mass% based on the total amount of solids in the curable resin composition. In the production process of the resin (B), from the viewpoint of developability and luminous intensity, preferably, no amine compound is used as a reaction catalyst. The content of the aliphatic tertiary amine compound and the aliphatic quaternary ammonium salt compound can be measured according to the measurement method in the Examples section described later. In the curable resin composition, the content of the aliphatic tertiary amine compound and the aliphatic quaternary ammonium salt compound may be, for example, less than 0.4 mass % relative to the total amount of solids in the curable resin composition.
[0039] In the curable resin composition, the mass ratio (solid content ratio) of the resin (B) to the photopolymerizable compound (C) described later may be, for example, 1 or more, and from the viewpoints of developability and luminescence intensity, is preferably 1.5 or more, more preferably 2 or more, and even more preferably 2.5 or more.
[0040] [3] Photopolymerizable compound (C) The photopolymerizable compound (C) is a compound that can be polymerized by an active radical, an acid, or the like generated from the photopolymerization initiator (D) described later, and examples thereof include a compound having an ethylenically unsaturated bond, and preferably a (meth)acrylic acid ester compound. In this specification, the term "(meth)acrylic acid" refers to at least one selected from the group consisting of acrylic acid and methacrylic acid. The terms "(meth)acryloyl" and "(meth)acrylate" have the same meaning.
[0041] Among them, the photopolymerizable compound (C) is preferably a polymerizable compound having three or more ethylenically unsaturated bonds. Examples of such polymerizable compounds include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol octa(meth)acrylate, tripentaerythritol hepta(meth)acrylate, tetrapentaerythritol deca(meth)acrylate, tetrapentaerythritol nona(meth)acrylate, tri ... Examples of the acrylates include 2-(2-(meth)acryloyloxyethyl)isocyanurate, ethylene glycol modified pentaerythritol tetra(meth)acrylate, ethylene glycol modified dipentaerythritol hexa(meth)acrylate, propylene glycol modified pentaerythritol tetra(meth)acrylate, propylene glycol modified dipentaerythritol hexa(meth)acrylate, caprolactone modified pentaerythritol tetra(meth)acrylate, and caprolactone modified dipentaerythritol hexa(meth)acrylate. The weight average molecular weight of the photopolymerizable compound (C) is preferably 150 or more and 2,900 or less, and more preferably 250 or more and 1,500 or less.
[0042] The content of the photopolymerizable compound (C) in the curable resin composition is, for example, preferably 7% by mass or more and 60% by mass or less, more preferably 10% by mass or more and 45% by mass or less, and even more preferably 13% by mass or more and 30% by mass or less, based on the total amount of solids in the curable resin composition. When the content of the photopolymerizable compound (C) is within the above range, the residual film rate of the cured pattern and the chemical resistance of the cured pattern tend to be further improved.
[0043] [4] Photopolymerization initiator (D) The photopolymerization initiator (D) is a compound that can generate active radicals, acids, etc. by the action of light or heat and initiate polymerization, and can include at least one selected from the group consisting of oxime compounds, biimidazole compounds, triazine compounds, and acylphosphine compounds. Among them, it is preferable to include at least one of oxime compounds and acylphosphine compounds. When these polymerization initiators are used, the residual film rate of the cured pattern is increased. When the above photopolymerization initiator is used, it tends to be easier to obtain a film that reduces the amount of outgas released by heating. In addition, when the above photopolymerization initiator is used, it tends to be easier to obtain a film that exhibits excellent solvent resistance. In addition, the above oxime compounds, biimidazole compounds, triazine compounds and acylphosphine compounds tend to have higher polymerization sensitivity during production of a cured film, and therefore are preferably compounds having at least two aromatic rings in the molecule. Examples of the aromatic ring include five-membered rings such as a furan ring, a pyrrole ring, an imidazole ring, a thiophene ring, and a thiazole ring, and six-membered rings such as a benzene ring, a pyridine ring, a pyrimidine ring, and a triazine ring, as well as condensed rings thereof.
[0044] The oxime compound is preferably an O-acyloxime compound, and is a compound having a partial structure represented by formula (d1). Hereinafter, * represents a bond. [ka]
[0045] Examples of the oxime compound include N-benzoyloxy-1-(4-phenylsulfanylphenyl)butan-1-one-2-imine, N-benzoyloxy-1-(4-phenylsulfanylphenyl)octan-1-one-2-imine, N-benzoyloxy-1-(4-phenylsulfanylphenyl)-3-cyclopentylpropan-1-one-2-imine, N-acetoxy-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethane-1-imine, N-acetoxy-1-[9-ethyl-6-{2-methyl-4-(3,3-dimethyl-2,4-dioxacyclopentyl]phenyl]ethane-1-imine, and N-acetoxy-1-[9-ethyl-6-{2-methyl-4-(3,3-dimethyl-2,4-dioxacyclopentyl]phenyl]ethane-1-imine. cyclopentanylmethyloxy)benzoyl}-9H-carbazol-3-yl]ethan-1-imine, N-acetoxy-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-3-cyclopentylpropan-1-imine, N-benzoyloxy-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-3-cyclopentylpropan-1-one-2-imine; compounds described in JP 2011-132215 A, WO 2008 / 78678, WO 2008 / 78686, and WO 2012 / 132558. Commercially available products such as Irgacure OXE01 and OXE02 (both manufactured by BASF), and N-1919 (manufactured by ADEKA) may also be used. Among them, the oxime compound is preferably at least one selected from the group consisting of N-benzoyloxy-1-(4-phenylsulfanylphenyl)butan-1-one-2-imine, N-benzoyloxy-1-(4-phenylsulfanylphenyl)octan-1-one-2-imine and N-benzoyloxy-1-(4-phenylsulfanylphenyl)-3-cyclopentylpropan-1-one-2-imine, and more preferably N-benzoyloxy-1-(4-phenylsulfanylphenyl)octan-1-one-2-imine.
[0046] The biimidazole compound is, for example, a compound represented by formula (d5). [ka] [In formula (d5), R 51 ~R 56 represents an aryl group having 6 to 10 carbon atoms which may have a substituent.]
[0047] Examples of the aryl group having 6 to 10 carbon atoms include a phenyl group, a toluyl group, a xylyl group, an ethylphenyl group, and a naphthyl group, and preferably a phenyl group. Examples of the substituent include a halogen atom and an alkoxy group having 1 to 4 carbon atoms. Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom, and preferably a chlorine atom. Examples of the alkoxy group having 1 to 4 carbon atoms include a methoxy group, an ethoxy group, a propoxy group, and a butoxy group, and preferably a methoxy group.
[0048] Examples of the biimidazole compound include 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetraphenylbiimidazole, 2,2'-bis(2,3-dichlorophenyl)-4,4',5,5'-tetraphenylbiimidazole (see, for example, JP-A-06-75372 and JP-A-06-75373), 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetraphenylbiimidazole, 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetra(alkoxyphenyl)biimidazole, and the like. phenyl)biimidazole, 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetra(dialkoxyphenyl)biimidazole, 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetra(trialkoxyphenyl)biimidazole (see, for example, JP-B-48-38403 and JP-A-62-174204), imidazole compounds in which the phenyl groups at the 4,4',5,5'-positions are substituted with carboalkoxy groups (see, for example, JP-A-7-10913), etc. Among these, the compounds represented by the following formula or mixtures thereof are preferred. [ka]
[0049] Examples of the triazine compound include 2,4-bis(trichloromethyl)-6-(4-methoxyphenyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxynaphthyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-piperonyl-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxystyryl)-1,3,5-triazine, and 2,4-bis(trichloromethyl)-6-[ 2-(5-methylfuran-2-yl)ethenyl]-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(furan-2-yl)ethenyl]-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(4-diethylamino-2-methylphenyl)ethenyl]-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(3,4-dimethoxyphenyl)ethenyl]-1,3,5-triazine, etc. Among them, 2,4-bis(trichloromethyl)-6-piperonyl-1,3,5-triazine is preferred.
[0050] Examples of the acylphosphine compound include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and (2,4,6-trimethylbenzoyl)diphenylphosphine oxide.
[0051] The above-mentioned photopolymerization initiators may be used alone or in combination of two or more photopolymerization initiators. When two or more photopolymerization initiators are used in combination, they may be combined with a known polymerization initiator other than the above-mentioned oxime compounds, biimidazole compounds, triazine compounds, and acylphosphine compounds.
[0052] Examples of known photopolymerization initiators include benzoin compounds such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether; benzophenone compounds such as benzophenone, methyl o-benzoylbenzoate, 4-phenylbenzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone, 2,4,6-trimethylbenzophenone, and 4,4'-bis(diethylamino)benzophenone; quinone compounds such as 9,10-phenanthrenequinone, 2-ethylanthraquinone, and camphorquinone; 10-butyl-2-chloroacridone, benzyl, methyl phenylglyoxylate, and titanocene compounds.
[0053] Other examples of photopolymerization initiators include 2,4,6-trimethylbenzoyldiphenylphosphine oxide (Speedcure TPO, manufactured by LAMBSON), 2,4,6-trimethylbenzoylphenylethoxyphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (OMNIRAD 819, manufactured by IGM RESINS), bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, 2-hydroxy-2-methyl-[4-(1-methylvinyl)phenyl]propanol oligomer (ESACURE ONE, manufactured by LAMBERTY), 2,2-dimethoxy-2-phenylacetophenone (OMNIRAD 651, manufactured by IGM RESINS), 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one (OMNIRAD 907, manufactured by IGM RESINS), and the like. Examples of the polymerization initiator include amines such as 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one (Omnirad 369, IGM Resins B.), 2-chlorothioxanthone, 2,4-dimethylthioxanthone, 2,4-diisopropylthioxanthone, isopropylthioxanthone, benzoic acid 2-dimethylaminoethyl ester, dimethylaminoacetophenone, p-dimethylaminobenzoic acid ethyl ester, and p-dimethylaminobenzoic acid isoamyl ester. Among other polymerization initiators, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one (Omnirad 907, IGM Resins B.) is preferred.
[0054] Examples of combinations of two or more photopolymerization initiators include combinations of an oxime compound and a biimidazole compound, an oxime compound and a triazine compound, an oxime compound and an acylphosphine compound, a biimidazole compound and a triazine compound, a biimidazole compound and an acylphosphine compound, and a triazine compound and an acylphosphine compound.
[0055] [Photopolymerization initiator aid (D1)] Furthermore, if necessary, a photopolymerization initiator aid (D1) may be used in combination. The photopolymerization initiator aid (D1) is a compound or sensitizer used to promote the polymerization of the photopolymerizable compound whose polymerization has been initiated by the photopolymerization initiator, and when the photopolymerization initiator aid (D1) is included, it is usually used in combination with the photopolymerization initiator. Examples of the photopolymerization initiator aid (D1) include amine compounds, alkoxyanthracene compounds, thioxanthone compounds, and carboxylic acid compounds.
[0056] Examples of the amine compound include triethanolamine, methyldiethanolamine, triisopropanolamine, methyl 4-dimethylaminobenzoate, ethyl 4-dimethylaminobenzoate, isoamyl 4-dimethylaminobenzoate, 2-dimethylaminoethyl benzoate, 2-ethylhexyl 4-dimethylaminobenzoate, N,N-dimethyl-p-toluidine, 4,4'-bis(dimethylamino)benzophenone (commonly known as Michler's ketone), 4,4'-bis(diethylamino)benzophenone, 4,4'-bis(ethylmethylamino)benzophenone, etc., and among these, 4,4'-bis(diethylamino)benzophenone is preferred. Commercially available products such as EAB-F (manufactured by Hodogaya Chemical Co., Ltd.) may also be used.
[0057] Examples of the alkoxyanthracene compound include 9,10-dimethoxyanthracene, 2-ethyl-9,10-dimethoxyanthracene, 9,10-diethoxyanthracene, 2-ethyl-9,10-diethoxyanthracene, 9,10-dibutoxyanthracene, and 2-ethyl-9,10-dibutoxyanthracene.
[0058] Examples of the thioxanthone compound include 2-isopropylthioxanthone, 4-isopropylthioxanthone, 2,4-diethylthioxanthone, 2,4-dichlorothioxanthone, and 1-chloro-4-propoxythioxanthone.
[0059] Examples of the carboxylic acid compound include phenylsulfanylacetic acid, methylphenylsulfanylacetic acid, ethylphenylsulfanylacetic acid, methylethylphenylsulfanylacetic acid, dimethylphenylsulfanylacetic acid, methoxyphenylsulfanylacetic acid, dimethoxyphenylsulfanylacetic acid, chlorophenylsulfanylacetic acid, dichlorophenylsulfanylacetic acid, N-phenylglycine, phenoxyacetic acid, naphthylthioacetic acid, N-naphthylglycine, and naphthoxyacetic acid.
[0060] The content of the photopolymerization initiator (D) is preferably 0.1 parts by mass or more and 300 parts by mass or less, more preferably 0.1 parts by mass or more and 200 parts by mass or less, based on 100 parts by mass of the photopolymerizable compound (C). The content of the photopolymerization initiator (D) is preferably 0.1 parts by mass or more and 30 parts by mass or less, more preferably 1 part by mass or more and 20 parts by mass or less, based on 100 parts by mass of the total amount of the resin (D) and the photopolymerizable compound (C). When the content of the photopolymerization initiator (D) is within the above range, the sensitivity tends to be increased and the exposure time tends to be shortened, thereby improving the productivity of the cured film. In addition, when the photopolymerization initiator aid (D1) is included, the content of the photopolymerization initiator aid (D1) is preferably 0.1 parts by mass or more and 300 parts by mass or less, more preferably 0.1 parts by mass or more and 200 parts by mass or less, based on 100 parts by mass of the photopolymerizable compound (C). The content of the photopolymerization initiator (D) is preferably 0.1 parts by mass or more and 30 parts by mass or less, more preferably 1 part by mass or more and 20 parts by mass or less, based on 100 parts by mass of the total amount of the resin (D) and the photopolymerizable compound (C). When the amount of the photopolymerization initiator aid (D1) is within this range, the cured film tends to be formed with even higher sensitivity.
[0061] [5] Antioxidants (E) The antioxidant (E) is not particularly limited as long as it is an antioxidant generally used industrially, and phenol-based antioxidants, phosphorus-based antioxidants, phosphorus / phenol complex-type antioxidants, sulfur-based antioxidants, etc. can be used. The antioxidant (E) may be used in combination of two or more kinds. The phosphorus / phenol complex-type antioxidant can be a compound having one or more phosphorus atoms and one or more phenol structures in the molecule. Among them, phosphorus / phenol complex-type antioxidants are preferred from the viewpoint of developability and luminescence intensity. In addition, when a phosphorus / phenol complex-type antioxidant is used, a film that reduces the amount of outgas released by heating tends to be easily obtained. In addition, when a phosphorus / phenol complex-type antioxidant is used, a film that exhibits excellent solvent resistance tends to be easily obtained.
[0062] Examples of the phenol-based antioxidant include Irganox (registered trademark) 1010 (Irganox 1010: pentaerythritol tetrakis [3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], manufactured by BASF Ltd.), Irganox 1076 (Irganox 1076: octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, manufactured by BASF Ltd.), Irganox 1330 (Irganox 1330: 3,3',3'',5,5',5''-hexa-t-butyl-a,a',a''-(mesitylene-2,4,6-triyl)tri-p-cresol, manufactured by BASF Ltd.), and Irganox 3114 (Irganox 3114: 1,3,5-tris(3,5-di-t-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, manufactured by BASF Co., Ltd.), 3790 (Irganox 3790: 1,3,5-tris((4-t-butyl-3-hydroxy-2,6-xylyl)methyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, manufactured by BASF Co., Ltd.), 1035 (Irganox 1035: thiodiethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], manufactured by BASF Co., Ltd.), 1135 (Irganox 1135: benzenepropanoic acid, 3,5-bis(1,1-dimethylethyl)-4-hydroxy, C7-C9 side chain alkyl ester, manufactured by BASF Co., Ltd.), 1520L (Irganox 1520L: 4,6-bis(octylthiomethyl)-o-cresol, manufactured by BASF Co., Ltd.), 3125 (Irganox 3125, manufactured by BASF Co., Ltd.), 565 (Irganox 565: 2,4-bis(n-octylthio)-6-(4-hydroxy-3',5'-di-t-butylanilino)-1,3,5-triazine, manufactured by BASF Co., Ltd.), Adeka STAB (registered trademark) AO-80 (Adeka STAB AO-80: 3,9-bis(2-(3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy)-1,1-dimethylethyl)-2,4,8,10-tetraoxaspiro(5,5) Undecane (manufactured by ADEKA Co., Ltd.), Sumilizer (registered trademark) BHT, Sumilizer GA-80, Sumilizer GS (all manufactured by Sumitomo Chemical Co., Ltd.), Cyanox (registered trademark) 1790 (manufactured by Cytec Co., Ltd.), and Vitamin E (manufactured by Eisai Co., Ltd.).
[0063] Examples of phosphorus-based antioxidants include Irgafos (registered trademark) 168 (Irgafos Irgafos 168: tris(2,4-di-t-butylphenyl)phosphite, manufactured by BASF Co., Ltd.), Irgafos 12 (Irgafos 12: tris[2-[[2,4,8,10-tetra-t-butyldibenzo[d,f][1,3,2]dioxaphosphine-6-yl]oxy]ethyl]amine, manufactured by BASF Co., Ltd.), Irgafos 38 (Irgafos 38: bis(2,4-bis(1,1-dimethylethyl)-6-methylphenyl)ethyl ester phosphorous acid, manufactured by BASF Co., Ltd.), Adekastab (registered trademark) 329K, Adekastab PEP36, Adekastab PEP-8 (all manufactured by ADEKA Co., Ltd.), Sandstab P-EPQ (manufactured by Clariant), Weston (registered trademark) 618, Adekastab 619G (all manufactured by GE), and Ultranox 626 (manufactured by GE).
[0064] Examples of phosphorus / phenol complex antioxidants include Sumilizer (registered trademark) GP (6-[3-(3-t-butyl-4-hydroxy-5-methylphenyl)propoxy]-2,4,8,10-tetra-t-butyldibenz[d,f][1.3.2]dioxaphosphepine) (manufactured by Sumitomo Chemical Co., Ltd.).
[0065] Examples of the sulfur-based antioxidant include dialkyl thiodipropionate compounds such as dilauryl, dimyristyl, and distearyl thiodipropionate, and β-alkyl mercaptopropionate compounds of polyols such as tetrakis[methylene(3-dodecylthio)propionate]methane.
[0066] The content of the antioxidant (E) may be, for example, 1 part by mass or more and 50 parts by mass or less relative to 100 parts by mass of the resin (B), and from the viewpoint of the amount of light emission and heat resistance, is preferably 5 parts by mass or more and 40 parts by mass or less, more preferably 7 parts by mass or more and 30 parts by mass or less, and even more preferably 11 parts by mass or more and 25 parts by mass or less.
[0067] [6] Leveling agent (F) The leveling agent (F) may be a silicone surfactant, a fluorine surfactant, or a silicone surfactant having a fluorine atom. These may have a polymerizable group in the side chain. From the viewpoint of developability and luminescence intensity, the leveling agent (F) is preferably a fluorine surfactant or a silicone surfactant.
[0068] Examples of silicone surfactants include surfactants having siloxane bonds in the molecule.Specific examples include Toray Silicone DC3PA, SH7PA, DC11PA, SH21PA, SH28PA, SH29PA, SH30PA, and SH8400 (trade name: manufactured by Toray Dow Corning Co., Ltd.), KP321, KP322, KP323, KP324, KP326, KP340, and KP341 (manufactured by Shin-Etsu Chemical Co., Ltd.), TSF400, TSF401, TSF410, TSF4300, TSF4440, TSF4445, TSF4446, TSF4452, and TSF4460 (manufactured by Momentive Performance Materials Japan LLC).
[0069] Examples of fluorine-based surfactants include surfactants having a fluorocarbon chain in the molecule.Specific examples include Fluorad (registered trademark) FC430, FC431 (manufactured by Sumitomo 3M Limited), Megafac (registered trademark) F142D, F171, F172, F173, F177, F183, F554, F575, R30, RS-718-K (manufactured by DIC Corporation), F-top (registered trademark) EF301, EF303, EF351, EF352 (manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.), Surflon (registered trademark) S381, S382, SC101, SC105 (manufactured by Asahi Glass Co., Ltd.) and E5844 (manufactured by Daikin Fine Chemicals Research Institute Co., Ltd.).
[0070] Examples of silicone surfactants having fluorine atoms include surfactants having a siloxane bond and a fluorocarbon chain in the molecule, such as Megafac (registered trademark) R08, BL20, F475, F477, and F443 (manufactured by DIC Corporation).
[0071] The content of the leveling agent (F) may be, for example, 0.001% by mass or more and 1.0% by mass or less, preferably 0.005% by mass or more and 0.75% by mass or less, more preferably 0.01% by mass or more and 0.5% by mass or less, and even more preferably 0.05% by mass or more and 0.5% by mass or less, based on the total amount of the curable resin composition. When the content of the leveling agent (F) is within the above range, the flatness of the cured film can be improved.
[0072] [7] Solvent (G) The solvent (G) is not particularly limited as long as it dissolves the resin (B), the photopolymerizable compound (C) and the photopolymerization initiator (D), and a solvent commonly used in the field can be used. For example, ester solvents (solvents containing -COO- and not containing -O- in the molecule), ether solvents (solvents containing -O- and not containing -COO- in the molecule), ether ester solvents (solvents containing -COO- and -O- in the molecule), ketone solvents (solvents containing -CO- and not containing -COO- in the molecule), alcohol solvents (solvents containing OH in the molecule and not containing -O-, -CO- and COO-), aromatic hydrocarbon solvents, amide solvents, dimethyl sulfoxide, etc. can be mentioned.
[0073] Examples of ester solvents include methyl lactate, ethyl lactate, n-butyl lactate, methyl 2-hydroxyisobutanoate, ethyl acetate, n-butyl acetate, isobutyl acetate, n-pentyl formate, isopentyl acetate, n-butyl propionate, isopropyl butyrate, ethyl butyrate, n-butyl butyrate, methyl pyruvate, ethyl pyruvate, propyl pyruvate, methyl acetoacetate, ethyl acetoacetate, cyclohexanol acetate, and γ-butyrolactone.
[0074] Examples of the ether solvent include ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, 3-methoxy-1-butanol, 3-methoxy-3-methylbutanol, tetrahydrofuran, tetrahydropyran, 1,4-dioxane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, diethylene glycol dipropyl ether, diethylene glycol dibutyl ether, anisole, phenetole, and methylanisole.
[0075] Examples of ether ester solvents include methyl methoxyacetate, ethyl methoxyacetate, butyl methoxyacetate, methyl ethoxyacetate, ethyl ethoxyacetate, methyl 3-methoxypropionate, ethyl 3-methoxypropionate, methyl 3-ethoxypropionate, ethyl 3-ethoxypropionate, methyl 2-methoxypropionate, ethyl 2-methoxypropionate, propyl 2-methoxypropionate, methyl 2-ethoxypropionate, ethyl 2-ethoxypropionate, methyl 2-methoxy-2-methyl ... Examples of the alkyl ether acetate include ethyl 2-methylpropionate, 3-methoxybutyl acetate, 3-methyl-3-methoxybutyl acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, diethylene glycol monoethyl ether acetate, and diethylene glycol monobutyl ether acetate.
[0076] Ketone solvents include 4-hydroxy-4-methyl-2-pentanone, acetone, 2-butanone, 2-heptanone, 3-heptanone, 4-heptanone, 4-methyl-2-pentanone, cyclopentanone, cyclohexanone, and isophorone.
[0077] Alcohol solvents include methanol, ethanol, propanol, butanol, hexanol, cyclohexanol, ethylene glycol, propylene glycol, and glycerin.
[0078] Aromatic hydrocarbon solvents include benzene, toluene, xylene, and mesitylene.
[0079] Amide solvents include N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.
[0080] The solvent is preferably propylene glycol monomethyl ether acetate, ethyl lactate, propylene glycol monomethyl ether, ethyl 3-ethoxypropionate, ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, 4-hydroxy-4-methyl-2-pentanone or toluene.
[0081] The solvent (G) is a component other than the solid content, and is a component that also includes the solvent contained in the quantum dots (A) and the resin (B). The content of the solvent (G) is the ratio of the total mass of all the solvents contained in the composition to the total amount of the composition, and may be, for example, 40% by mass or more and 95% by mass or less, and preferably 55% by mass or more and 90% by mass or less, relative to the total amount of the curable resin composition. In other words, the solid content of the curable resin composition is preferably 5% by mass or more and 60% by mass or less, more preferably 10% by mass or more and 45% by mass or less. When the content of the solvent (G) is within the above range, the flatness of the composition layer during application is improved, and a cured film with an appropriate film thickness tends to be easily formed.
[0082] [8] Light scattering agent (H) The curable resin composition of the present invention may further contain a light scattering agent (H). Examples of the light scattering agent (H) include metal or metal oxide particles, glass particles, etc. Examples of metal oxides include TiO2, SiO2, BaTiO3, ZnO, etc. The particle size of the light scattering agent (I) is, for example, about 0.03 μm or more and 20 μm or less, preferably 0.05 μm or more and 1 μm or less, and more preferably 0.05 μm or more and 0.5 μm or less.
[0083] The content of the light scattering agent (H) in the curable resin composition may be, for example, 0.001% by mass or more and 50% by mass or less, based on the total amount of solids in the curable resin composition, and is preferably 1% by mass or more and 30% by mass or less, more preferably 2% by mass or more and 10% by mass or less, from the viewpoint of developability and luminescence intensity. When the curable composition contains an organic solvent, the light scattering agent (H) may be dispersed in advance in a part of the organic solvent (G) using a dispersant (J). Commercially available products can be used as the dispersant (J). Examples of commercially available products include: DISPERBYK-101, 102, 103, 106, 107, 108, 109, 110, 111, 116, 118, 130, 140, 154, 161, 162, 163, 164, 165, 166, 170, 171, 174, 180, 181, 182, 183, 184, 185, 190, 192, 200 manufactured by BYK Japan 0, 2001, 2020, 2025, 2050, 2070, 2095, 2150, 2155;ANTI-TERRA-U, U100, 203, 204, 250,;BY K-P104, P104S, P105, 220S, 6919; BYK-LPN6919, 21116; LACTIMON, LACTIMON-WS; Bykumen, etc.; Lubrizol Japan SOLSPERSE-3000, 9000, 13000, 13240, 13650, 13940, 16000, 17000, 18000, 20000, 21000, 24000, 26000, 27000, 28000, 31845, 32000, 32500, 32550, 33500, 32600, 34750, 35100, 36600, 38500, 41000, 41090, 53095, 55000, 76500, etc. BASF EFKA-46, 47, 48, 452, 4008, 4009, 4010, 4015, 4020, 4047, 4050, 4055, 4060, 4080, 4400, 4401, 4402, 4403, 4406, 4408, 4300, 4310, 4320, 4330, 4340, 450, 451, 453, 4540, 4550, 4560, 4800, 5010, 5065, 5066, 5070, 7500, 7554, 1101, 120, 150, 1501, 1502, 1503, etc.; Ajinomoto Fine-Techno Co., Ltd. Ajisper PA111, PB711, PB821, PB822, PB824 etc.
[0084] In addition, the curable resin composition of the present invention may further contain additives known in the technical field, such as a polymerization inhibitor, a filler, another polymer compound, an adhesion promoter, a light stabilizer, and a chain transfer agent, as necessary.
[0085] <Method for producing curable resin composition> The method for producing the curable resin composition can include a step of mixing the quantum dots (A), the resin (B), the polymerizable compound (C), the photopolymerization initiator (D), the antioxidant (E), the leveling agent (F) and the solvent (G), as well as other components used as necessary.
[0086] The method for producing a curable resin composition of the present invention can include a step of preparing a resin (B). The obtained resin (B) does not contain any aliphatic tertiary amine compound and aliphatic quaternary ammonium salt compound, or can contain at least one of an aliphatic tertiary amine compound and an aliphatic quaternary ammonium salt compound in an amount of less than 0.8 mass% based on the total amount of the solid content of the resin (B). In the step of preparing the resin (B), it is preferable not to use an amine compound as a reaction catalyst from the viewpoint of development time and luminescence intensity.
[0087] <Cured film> The cured film of the present invention can be obtained by applying the curable resin composition of the present invention to a substrate and curing it by the action of light or heat. The cured film of the present invention may be formed on the entire surface of the substrate, or may be formed on a part of the substrate (i.e., a cured pattern). Methods for forming a cured film on a part of the substrate include photolithography, inkjet, and printing. Among them, photolithography is preferred. The photolithography is a method in which the curable resin composition of the present invention is applied to a substrate, dried as necessary to form a composition layer, and the composition layer is exposed through a photomask and developed. Examples of a method for forming a cured film over the entire surface of a substrate include a method in which the curable resin composition of the present invention is applied to a substrate, and dried as necessary to form a composition layer, and the composition layer is heated and / or the entire surface of the composition layer is exposed to light.
[0088] Examples of the substrate include glass plates such as quartz glass, borosilicate glass, alumina silicate glass, and soda lime glass with a silica-coated surface; resin plates such as polycarbonate, polymethyl methacrylate, and polyethylene terephthalate; silicon; and the above-mentioned substrates on which thin films of aluminum, silver, and silver / copper / palladium alloys are formed.
[0089] The formation of a cured pattern by photolithography can be carried out using known or conventional devices and conditions. For example, the pattern can be produced as follows. First, the curable composition is applied onto a substrate, and volatile components such as the solvent are removed by heating and drying (pre-baking) and / or drying under reduced pressure to obtain a composition layer. Examples of the application method include spin coating, slit coating, and slit and spin coating. The temperature when drying by heating is preferably 30 to 120° C., more preferably 50 to 110° C. The heating time is preferably 10 seconds to 60 minutes, more preferably 30 seconds to 30 minutes. When drying is carried out under reduced pressure, it is preferable to carry out the drying under a pressure of 50 to 150 Pa and at a temperature in the range of 20 to 25°C. The film thickness of the composition layer is not particularly limited and may be appropriately selected depending on the film thickness of the desired cured pattern, and may be, for example, 0.5 μm or more and 20 μm or less, preferably 3 μm or more and 18 μm or less, and more preferably 5 μm or more and 16 μm or less.
[0090] The composition layer is then exposed through a photomask to form a desired cured pattern, the pattern on which is not particularly limited. The light source used for exposure is preferably a light source that generates light with a wavelength of 250 to 450 nm. For example, from the light with this wavelength, light with a wavelength of around 436 nm, around 408 nm, or around 365 nm may be selectively extracted by a bandpass filter according to the absorption wavelength of the polymerization initiator. Specifically, mercury lamps, light-emitting diodes, metal halide lamps, halogen lamps, etc. may be mentioned. It is preferable to use an exposure device such as a mask aligner or a stepper, since it is possible to uniformly irradiate the entire exposure surface with parallel light rays and to accurately align the photomask with the substrate on which the composition layer is formed. The exposed composition layer is cured by polymerization of the polymerizable compound, etc. contained in the composition layer.
[0091] By contacting the composition layer after exposure with a developer and developing it, the unexposed portion of the composition layer is dissolved and removed in the developer, and a cured pattern is obtained. Examples of the developer include an aqueous solution of an alkaline compound such as potassium hydroxide, sodium bicarbonate, sodium carbonate, and tetramethylammonium hydroxide, and an organic solvent. The concentration of the alkaline compound in the aqueous solution is preferably 0.01% by mass or more and 10% by mass or less, and more preferably 0.03% by mass or more and 5% by mass or less. Examples of the organic solvent include the same as the above-mentioned solvent (G). Furthermore, the developer may contain a surfactant. The developing method may be any of a puddle method, a dipping method, a spray method, etc. Furthermore, the substrate may be inclined at an arbitrary angle during the developing.
[0092] The cured pattern obtained by development is preferably further heated (post-baked). The heating temperature is preferably 150 to 250° C., more preferably 160 to 235° C. The heating time is preferably 1 to 120 minutes, more preferably 10 to 60 minutes. By heating after development, polymerization of unreacted polymerizable compounds contained in the cured pattern can be promoted, and therefore a cured pattern with better chemical resistance can be obtained.
[0093] By irradiating the cured film with ultraviolet light or visible light, the cured film of the present invention can emit light with a wavelength different from that of the irradiated light. By selecting the components and particle size of the quantum dots in the curable resin composition used to form the cured film of the present invention, the wavelength of the emitted light can be selected. The cured film of the present invention has a function of converting the wavelength of irradiated light as described above, and therefore can be used as a color conversion layer of a display device. Examples of such a display device include the display devices described in JP2006-309219A, JP2006-310303A, JP2013-15812A, JP2009-251129A, and JP2014-2363A.
[0094] The cured film of the present invention can easily reduce the amount of outgassing released when heated. The amount of outgassing can be evaluated according to the method described in the Examples section below as the weight change rate (%) [= ([weight after heating] / [weight before heating]) × 100] when the cured film is heated at 180 ° C. for 60 minutes. The weight change rate (%) of the cured film of the present invention may be, for example, 1% or less, or 0.5% or less. From the viewpoint of easily reducing contamination of the equipment in the subsequent process, it is preferably 0.8% or less, more preferably 0.6% or less, even more preferably 0.4% or less, particularly preferably 0.2% or less, and usually 0% or more, for example 0.01% or more or 0.05% or more.
[0095] The cured film of the present invention can exhibit excellent solvent resistance. The solvent resistance can be evaluated according to the method described in the Examples section as the rate of change in luminous intensity when the cured film is immersed in propylene glycol monomethyl ether acetate (PGMEA) for 30 minutes. The cured film of the present invention may have a rate of change in luminous intensity of, for example, 88% or more, and from the viewpoint of increasing brightness, the rate of change is preferably 90% or more, more preferably 92% or more, even more preferably 94% or more, particularly preferably 96% or more, and even more particularly preferably 98% or more, and may usually be 100% or less.
[0096] The cured film of the present invention preferably has a weight change rate (%) of 0.8% or less when heated at 180°C for 60 minutes, and a change rate of 92% or more in emission intensity when immersed in PGMEA for 30 minutes. The cured film of the present invention preferably has a weight change rate (%) of 0.4% or less when heated at 180°C for 60 minutes, and a change rate of 88% or more in emission intensity when immersed in PGMEA for 30 minutes. It is particularly preferable that the cured film of the present invention has a weight change rate (%) of 0.4% or less when heated at 180°C for 60 minutes, and a change rate of 92% or more in emission intensity when immersed in PGMEA for 30 minutes.
[0097] The curable resin composition of the present invention tends to provide a film with high luminescence intensity and a high development speed even in a thick film, and is therefore useful as a color conversion layer in a display device, particularly a liquid crystal display device. EXAMPLES
[0098] The present invention will be described in more detail below with reference to examples. In the examples, "%" and "parts" are by mass % and parts by mass unless otherwise specified.
[0099] [Evaluation of developability] The curable resin composition was applied to a 5 cm square glass substrate (Eagle 2000; Corning) by spin coating to a film thickness of 10 μm, and then prebaked at 100° C. for 3 minutes to form a curable resin composition layer, which was then immersed in a developer (aqueous solution of 0.05% potassium hydroxide) for development. The time until the curable resin composition layer was completely removed was measured.
[0100] [Measurement of luminescence intensity] The curable resin composition was applied by spin coating onto a 5 cm square glass substrate (Eagle 2000; Corning Incorporated) to a film thickness of 10 μm, and then prebaked at 100° C. for 3 minutes to form a curable composition layer. The substrate on which the curable composition layer was formed was exposed to 80 mJ / cm 2 in the air using an exposure machine (TME-150RSK; Topcon Corporation).2 After development, the coating was post-baked at 180° C. for 60 minutes to obtain a substrate having a cured film. A narrow-angle sensing backlight (OPF series; manufactured by Optex FA) equipped with an LED lamp with an emission wavelength of 444 nm and a scratch-resistant cover was prepared as the backlight. The backlight was placed with the scratch-resistant cover facing up, and a black film with holes was placed on the scratch-resistant cover to prevent light leakage from areas other than the measurement points. An optical fiber for detecting the emission light, connected to the spectrometer described below, was then placed at a height of 4 cm from the surface of the scratch-resistant cover. A glass substrate (Eagle 2000; manufactured by Corning) was placed as a reference on the surface of the scratch-resistant cover of the backlight. In this state, the backlight was turned on, and the light intensity of the backlight was adjusted so that the total radiant flux (μW) of the backlight was 1500 μW through the reference glass substrate (Eagle 2000; manufactured by Corning). Next, the substrate having the cured film prepared above was placed on the surface of the glass substrate. In this state, the backlight was turned on, and the luminous intensity (unit: μW) of the light emitted from the cured film was measured as the integrated radiant flux in the wavelength range of 485 nm to 780 nm. A spectrometer (manufactured by Ocean Optics) was used to measure the luminous intensity.
[0101] [Method for evaluating outgassing] A cured film was prepared in the same manner as described above in [Measurement of luminescence intensity], and then the film portion (film thickness = 10 µm) was peeled off and held at 180°C for 60 minutes using TGDTA [high-performance thermal analyzer NEXTA (registered trademark) STA200 (manufactured by Hitachi High-Tech Corporation)], after which the weight change rate (%) [= ([weight after heating] / [weight before heating]) × 100] was determined.
[0102] [Method for evaluating solvent resistance] After preparing a cured film in the same manner as in [Measurement of luminescence intensity] above, the film was immersed in PGMEA for 30 minutes. The luminescence intensity was measured before and after immersion, and the rate of change in the luminescence intensity before and after the immersion was calculated.
[0103] [Weight average molecular weight] The weight average molecular weight (Mw) of the resin was measured by GPC under the following conditions. Equipment: K2479 (Shimadzu Corporation) Column: SHIMADZU Shim-pack GPC-80M Column temperature: 40°C Solvent: Tetrahydrofuran Flow rate; 1.0mL / min Detector: RI Calibration standard material: TSK STANDARD POLYSTYRENE F-40, F-4, F-288, A-2500, A-500 (manufactured by Tosoh Corporation)
[0104] [Acid value] 3 g of the resin solution was precisely weighed and dissolved in a mixed solvent of 90 g of acetone and 10 g of water. Using a 0.1 N KOH aqueous solution as a titrant, the acid value of the polymer solution was measured with an automatic titrator (manufactured by Hiranuma Sangyo Co., Ltd., product name: COM-555). The acid value per 1 g of solids (AV) was calculated from the acid value of the solution and the solids content of the solution.
[0105] [Solid content] Approximately 1 g of the polymer solution was weighed out in an aluminum cup, dried at 180° C. for 1 hour, and then the mass was measured. The solid content (mass%) of the polymer solution was calculated from the amount of mass loss.
[0106] [Content of aliphatic tertiary amine compound and aliphatic quaternary ammonium salt compound] <Device name, measurement conditions> Equipment used: Thermo Fisher Scientific ICS-1500 Separation column: IonPac CG14+CS14 (4 mm) Column temperature: 30℃ Eluent: 10mM methanesulfonic acid Flow rate: 1mL / min Detector: Electrical conductivity detector <Pretreatment method> 0.1 g of the sample was dissolved in THF and the volume was adjusted to 10 mL with pure water. The solution was filtered and the filtrate was further diluted with pure water to prepare the test solution.
[0107] Production Example 1: Quantum dot dispersion (A-1) A toluene dispersion of InP / ZnSeS quantum dots coordinated with oleic acid as a ligand was prepared. The dispersion was distilled under reduced pressure to remove the toluene. 70 parts of cyclohexyl acetate were added to 30 parts of solids to obtain quantum dot dispersion (A-1) (solids 30%).
[0108] Production Example 2: Light scattering agent (H-1) To 70 parts by mass of titanium oxide nanoparticles, 3 parts by mass of DISPERBYK21116 (manufactured by BYK Japan) in terms of solid content and PGMEA were added until the total amount was 100 parts by mass, and the mixture was stirred with a paint shaker until sufficiently dispersed to obtain a dispersion of scattering agent (H-1) (solid content 73%).
[0109] Synthesis example 1: Resin (B-1) 110 parts by mass of propylene glycol monomethyl ether acetate (hereinafter referred to as "PGMEA") was added to a flask equipped with a stirrer, a reflux condenser with a thermometer, a dropping funnel, and a nitrogen inlet tube, and the mixture was stirred while replacing with nitrogen and heated to 80° C. A solution of 25 parts by mass of dicyclopentanyl methacrylate, 26 parts by mass of methyl methacrylate, 16 parts by mass of methacrylic acid, and 14 parts by mass of 2,2'-azobis(2,4-dimethylvaleronitrile) in 110 parts by mass of PGMEA was dropped from the dropping funnel into the flask, and the mixture was stirred at 80° C. for 3 hours. Next, 16 parts by mass of glycidyl methacrylate, 0.4 parts by mass of 2,2'-methylenebis(4-methyl-6-t-butylphenol), and 0.8 parts by mass of triphenylphosphine were added to the flask, and the temperature was raised to 110°C. The mixture was stirred for 8 hours to react the carboxylic acid and epoxy group in the polymer, thereby introducing a polymerizable unsaturated bond. Next, 17 parts by mass of 1,2,3,6-tetrahydrophthalic anhydride were added and the reaction was continued for 3 hours to introduce a carboxylic acid group into the side chain. The reaction solution was cooled to room temperature to obtain a resin (B-1) solution. The resin (B-1) had a weight average molecular weight of 5,200 and an acid value of 100 mgKOH / g, and the solid content in the resin (B-1) solution was 40 mass %.
[0110] Synthesis example 2: Resin (B-2) A resin (B-2) solution was prepared in the same manner as in Synthesis Example 1, except that the amount of 2,2'-azobis(2,4-dimethylvaleronitrile) was 12.5 parts by mass.
[0111] Synthesis example 3: Resin (B-3) A resin (B-3) solution was prepared in the same manner as in Synthesis Example 1, except that the amount of 2,2'-azobis(2,4-dimethylvaleronitrile) was changed to 11 parts by mass.
[0112] Synthesis example 4: Resin (B-4) A resin (B-4) solution was prepared in the same manner as in Synthesis Example 1, except that the amounts of methyl methacrylate, methacrylic acid, and 2,2'-azobis(2.4-dimethylvaleronitrile) were 23 parts by mass, 19 parts by mass, and 10 parts by mass, respectively.
[0113] Synthesis example 5: Resin (B-5) 110 parts by mass of propylene glycol monomethyl ether acetate (hereinafter referred to as "PGMEA") was added to a flask equipped with a stirrer, a reflux condenser with a thermometer, a dropping funnel, and a nitrogen inlet tube, and the mixture was stirred while replacing with nitrogen and heated to 80° C. A solution of 25 parts by mass of dicyclopentanyl methacrylate, 21 parts by mass of methyl methacrylate, 26 parts by mass of methacrylic acid, and 10 parts by mass of 2,2'-azobis(2.4-dimethylvaleronitrile) in 110 parts by mass of PGMEA was dropped from the dropping funnel into the flask, and the mixture was stirred at 80° C. for 3 hours. Next, 16 parts by mass of glycidyl methacrylate, 0.4 parts by mass of 2,2'-methylenebis(4-methyl-6-t-butylphenol), and 0.8 parts by mass of triethylamine were added to the flask, heated to 110°C, and stirred for 8 hours to react the carboxylic acid and epoxy group in the polymer and introduce a polymerizable unsaturated bond. The reaction solution was cooled to room temperature to obtain a resin (B-5) solution. The content of triethylamine in the resin (B-5) was 0.8% by mass relative to the total amount of solids in the resin (C-5).
[0114] Synthesis example 6: Resin (B-6) A flask equipped with a cooling tube and a stirrer was charged with 150 parts by mass of propylene glycol monomethyl ether acetate and substituted with nitrogen. The mixture was heated to 80°C, and a mixed solution of 50 parts by mass of propylene glycol monomethyl ether acetate, 30 parts by mass of 2-methacryloyloxyethyl succinic acid, 10 parts by mass of benzyl methacrylate, 60 parts by mass of 2-ethylhexyl methacrylate, and 6 parts by mass of 2,2'-azobis(2,4-dimethylvaleronitrile) was dropped over 2 hours at the same temperature, and the mixture was polymerized for 1 hour while maintaining the temperature. Thereafter, the temperature of the reaction solution was raised to 90°C, and the mixture was polymerized for another 1 hour to obtain a resin (B-6) solution. The resin (B-6) had Mw=11000, an acid value=70, and the resin (B-6) solution had a solids concentration=33% by mass.
[0115] The weight average molecular weight, molecular weight distribution, acid value, acrylic equivalent, and contents of aliphatic tertiary amine and aliphatic quaternary ammonium salt compound of resins (B-1) to (B-6) are shown in Table 1 below.
[0116] [Table 1]
[0117] <Examples 1 to 9, Comparative Example 1> The components in Table 2 were mixed to prepare curable resin compositions of Examples and Comparative Examples. The luminescence intensity and development time of the obtained curable resin compositions were evaluated. The results are shown in Table 3.
[0118] [Table 2]
[0119] Photopolymerizable compound (C-1): M-510 (polybasic modified acrylate, manufactured by Toagosei Co., Ltd.) Photopolymerizable compound (C-2): A-9550 (dipentaerythritol polyacrylate, manufactured by Shin-Nakamura Chemical Co., Ltd.) Photopolymerization initiator (D-1): Oxe01 (manufactured by BASF) Photopolymerization initiator (D-2): Omnirad 907 (manufactured by IGM Resins BV) Antioxidant (E-1): Sumilizer-GP (phosphorus / phenol complex type, antioxidant, manufactured by Sumitomo Chemical Co., Ltd.) Antioxidant (E-2): AO-60 (phenolic antioxidant, manufactured by ADEKA) Leveling agent (F-1): SH8400 (silicone-based leveling agent, manufactured by Toray Dow Co., Ltd.) Leveling agent (F-2): F-554 (fluorine-based leveling agent, manufactured by DIC) Solvent (G-1): PGMEA (propylene glycol monomethyl ether acetate) Solvent (G-2): Cyclohexyl acetate
[0120] [Table 3]
Claims
1. The present invention includes a quantum dot (A), a resin (B), a photopolymerizable compound (C), a photopolymerization initiator (D), an antioxidant (E), a leveling agent (F), and a solvent (G), The resin (B) is a curable resin composition having a weight average molecular weight in terms of polystyrene of less than 10,000 and an acid value of 90 mgKOH / g or more and 150 mgKOH / g or less, The content of the quantum dots (A) is 5% by mass or more and 50% by mass or less based on the total amount of solids in the curable resin composition, The content of the resin (B) is 13% by mass or more and 60% by mass or less based on the total amount of solids in the curable resin composition, A curable resin composition, wherein a mass ratio (solid content ratio) of the resin (B) to the photopolymerizable compound (C) is 2 or more.
2. The curable resin composition according to claim 1 , wherein the resin (B) contains a resin having an acrylic equivalent of 300 g / eq or more and 2,000 g / eq or less.
3. The curable resin composition according to claim 1 , wherein the photopolymerization initiator (D) comprises an oxime compound.
4. The curable resin composition according to any one of claims 1 to 3, wherein the antioxidant (E) comprises a phosphorus / phenol complex type antioxidant.
5. The curable resin composition according to any one of claims 1 to 4, wherein the leveling agent (F) contains a fluorine-based surfactant or a silicone-based surfactant.
6. The curable resin composition according to any one of claims 1 to 5, which does not contain any aliphatic tertiary amine compound and any aliphatic quaternary ammonium salt compound, or contains at least one of an aliphatic tertiary amine compound and an aliphatic quaternary ammonium salt compound in an amount of less than 0.4 mass% relative to the total amount of solids in the curable resin composition.
7. A cured film formed from the curable resin composition according to any one of claims 1 to 6.
8. A display device comprising the cured film according to claim 7.
9. A method for producing the curable resin composition according to claim 1, The resin (B) is prepared. The resin (B) does not contain any aliphatic tertiary amine compound or aliphatic quaternary ammonium salt compound, or contains at least one of an aliphatic tertiary amine compound and an aliphatic quaternary ammonium salt compound in an amount of less than 0.8 mass% based on the total amount of solids in the resin (B).
10. The method according to claim 9, wherein in the step of preparing the resin (B), no amine compound is used as a reaction catalyst.
Citation Information
Patent Citations
Curable resin composition
JP2013064989A
Colored curable resin composition
JP2013203955A
Curable resin composition, cured film, wavelength conversion film, light-emitting element, and method for forming light-emitting layer
JP2016065178A
Self-luminous photosensitive resin composition, and color filter and image display device manufactured by using the same
JP2016157118A
Colored curable resin composition
JP2019139240A